Analysis of The Main Character's Conflicts in The Novel The Picture of Dorian Gray by Oscar Wilde - Mamesah, Esther Charenina Yulia; Junaedi, Sony (LINGUAMEDIA Journal, 2024)
This study aims to analyze “The Picture of Dorian Gray”, a novel by Oscar Wilde. The topic of the research is the conflicts that happen in the character, and how the main character’s build the conflicts which are portrayed in The Picture of Dorian Gray. The purpose of this study is to analyze the conflicts. There are two kinds of conflict, namely internal conflict and external conflict, but this study only focuses on internal conflict. The methodology of this study used the descriptive qualitative method. A research method that emphasizes the elements contained in literary works such as characters, plot particularly about the internal conflict. This research uses Objective approach by M.H Abrams, intrinsic theories by Wellek and Warren. The results of this study, first, the writer explain about the internal conflicts are analyzed that is including physical conflicts, psychological conflicts, mental conflicts, moral conflicts, emotional conflicts. This study focuses on the conflicts that happen in the main characters. Meanwhile the main character’s builds the conflict has through the following steps: a) The beginning of conflict; b) The rising of conflict; c) The climax of conflict; d) The falling of conflict; e) The ending of conflict. Then, what are the conflicts experienced by the main characters in the novel. The writer concludes that the conflicts in the novel The Picture of Dorian Gray, especially the internal conflicts that exist in the main character using the theory that has been mentioned above. Keywords: Main Character, Conflict, Intrinsic Theory, The Picture of Dorian Gray.